2009
DOI: 10.1037/a0015109
|View full text |Cite
|
Sign up to set email alerts
|

Violated expectations and acculturative stress among U.S. Hispanic immigrants.

Abstract: Expectancy violation theory (EVT) was tested with 112 Hispanic immigrants living in the United States by determining whether discrepancies between their retrospectively recalled pre-migration expectations about life in the United States and their post-migration (actual) experiences in the United States would predict their levels of acculturative stress. Discrepancies were assessed in 4 domains (ability to communicate with English speakers, perceiving their communities and the United States as safe, obtaining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 57 publications
3
60
2
Order By: Relevance
“…However, these studies assume a loss without examining the pre-immigration context. An exception to this is a recent study by Negy and colleagues (2009) who found that the pre-immigration expectations of how life was going to be in the U.S. were related to acculturative stress. For Latino immigrants, the more discrepancy between expectations of how life in the U.S. would be like and what it actually is, the more acculturative stress is reported (Negy, Hammons, Reig-Ferrer, & Carper, 2010).…”
Section: Literature Reviewmentioning
confidence: 89%
“…However, these studies assume a loss without examining the pre-immigration context. An exception to this is a recent study by Negy and colleagues (2009) who found that the pre-immigration expectations of how life was going to be in the U.S. were related to acculturative stress. For Latino immigrants, the more discrepancy between expectations of how life in the U.S. would be like and what it actually is, the more acculturative stress is reported (Negy, Hammons, Reig-Ferrer, & Carper, 2010).…”
Section: Literature Reviewmentioning
confidence: 89%
“…The majority of Latina immigrant women in this study had lived in the U.S. for many years and had time to reconcile to the reality of living in the U.S. However, it might be difficult to generalize how unmet expectations impact acculturative stress, since being content with different aspects of life in a new country impacts acculturative stress differently [29].…”
Section: Discussionmentioning
confidence: 99%
“…The following external contextual factors have been linked with acculturative stress: perceived discrimination [35], citizenship and immigration status [3], unemployment [18], U.S. lifestyle, lower levels of education [15], the presence of adolescents in the household [14], and lack of adequate income [23]. Social support [2,26] and positive expectations about the U.S. [15,29] were associated with low acculturative stress. Internal contextual variables associated with acculturative stress include religiosity (religious participation) 5, and personality characteristics [25].…”
Section: Additional External and Internal Contextsmentioning
confidence: 99%
“…Only two studies (Feldman, 2005; Negy, Schwartz, & Reig-Ferrer, 2009) have been designed to understand the influences of such ‘personal’ EVs and each of these examined negative emotionality as outcomes. Feldman (2005) found mixed support for the idea that EVs surrounding a negative life event predict negative emotions.…”
Section: Expectancy Violationsmentioning
confidence: 99%